SIKAP SISWA: BAGAIMANA DAMPAKNYA PADA KEDISIPLINAN BELAJAR SISWA DI SEKOLAH? STUDI META-ANALISIS - Purwandari, Eny; Putra, Erlangga Anantayudha Nursahid (Program Studi S1 Psikologi, 2023)
This meta-analysis study aims to analyze the effect of student attitudes on student learning discipline with precise values using sample data from previous larger studies. The use of meta-analysis is also to collect various findings from previous studies to see differences in attitudes and discipline in various schools. Data from this study were obtained from searching scientific articles published in national or international journals with a range of 2012-2021. The sample of this study were 9 articles that met the criteria. Journal article database sources from keywords related to student attitudes and discipline. The overall results of this study obtained a final correlation coefficient of 0.848. The sampling error and measurement error in this study is small (4.02%). On the other hand, the results of the study also explain that SMA/SMK students have a better attitude than junior high school students to improve discipline. Where the mean value of SMA/SMK students is 0.75 with an SD value of 0.18 and SMP students is 0.69 with an SD value of 0.21. Future research should pay more attention to how the distribution of countries and other variable factors that affect discipline besides student attitudes.